PERANAN BPOM KABUPATEN BULELENG DALAM HAL PENGAWASAN OBAT DAN MAKANAN DALAM PERLINDUNGAN KONSUMEN - Ida Ayu Kade Novi Handayani; Si Ngurah Ardhya; Ketut Sudiatmaka (Jurnal Ilmu Hukum Sui Generis, 2023)
This study aims to identify and analyze the role of BPOM Buleleng Regency in supervising drug and food products and the obstacles encountered in supervising drug and food products. In this study, the type of research used is empirical legal research with a descriptive nature that aims to accurately describe individual characteristics, circumstances, determine the spread of a symptom, or determine whether there is a relationship between a symptom and other symptoms in society. The data and data sources used are primary data obtained directly in the field, namely the Pom Workshop, Buleleng Regency, secondary data obtained from the legal foundations related to this research with primary materials containing basic norms, secondary legal materials regarding books related to this research. In data collection techniques using documentation/library study techniques, interview techniques and observation techniques with qualitative processing and analysis techniques. The results of this study indicate that the role of the Pom Loka Buleleng Regency as an organization that is responsible for carrying out rights and obligations as drug and food supervisors in accordance with applicable laws and regulations, then the obstacles encountered by the Buleleng Regency Pom Loka in supervising drugs and food occur due to two factors, namely, internal factors (all-online system) due to limited human resources and lack of participation of law enforcement officials and external factors (lack of consumer understanding of a product in circulation) rampant circulation of illegal products online and low public knowledge and awareness about the dangers of counterfeit products.